An update of clinical experience with the quadrivalent meningococcal ACWY-CRM conjugate vaccine - Pavitra Keshavan; Michele Pellegrini; Kumaran Vadivelu-Pechai; Michael Nissen (Taylor & Francis Group, 2018)
Introduction: Menveo, quadrivalent meningococcal ACWY-CRM conjugate vaccine, was first licensed in 2010 in the United States and has a long track record of immunogenicity and safety in all age groups, including infants from 2 months of age. Areas covered: This review presents clinical and post-marketing experience with MenACWY-CRM from 32 studies conducted in 20 countries that included individuals aged from 2 months to 75 years. Expert commentary: This decade has seen an increased number of countries reporting serogroup W ST-11 clonal complex outbreaks of invasive meningococcal disease. As infant vaccination programs targeting the meningococcus are reevaluated, the role of quadrivalent meningococcal vaccines including MenACWY-CRM will be expanded. MenACWY-CRM was immunogenic in all populations and age groups studied, regardless of country of origin. MenACWY-CRM can be coadministered with many routinely used infant, toddler and adolescent vaccines, and traveler vaccines in adults, allowing for flexible use within national immunization programs and recommendations. Antibody persistence has been demonstrated up to 5 years post vaccination in all age groups. Booster doses induced robust increases in antibody titers for all four serogroups, indicative of effective priming and induction of immunological memory. The acceptable safety profile of MenACWY-CRM has been confirmed in large post-marketing safety studies.